The Robot@Home2 dataset: A new release with improved usability tools - Ambrosio Cestero, Gregorio; Ruiz-Sarmiento, José Raúl; González-Jiménez, Antonio Javier (Elsevier, 2023)
Released in 2017, Robot@Home is a dataset captured by a mobile robot during indoor navigation sessions in apartments. This paper presents Robot@Home2, an enhanced version of the Robot@Home dataset, aimed at improving usability and functionality for developing and testing mobile robotics and computer vision algorithms. Robot@Home2 consists of three main components. Firstly, a relational database that states the contextual information and data links, compatible with Standard Query Language. Secondly,a Python package for managing the database, including downloading, querying, and interfacing functions. Finally, learning resources in the form of Jupyter notebooks, runnable locally or on the Google Colab platform, enabling users to explore the dataset without local installations. These freely available tools are expected to enhance the ease of exploiting the Robot@Home dataset and accelerate research in computer vision and robotics.
Keywords: Sistemas informáticos; Robótica; Algoritmos computacionales; Visión artificial (Robótica); Bases de datos relacionales; Dataset; Mobile robotics; Relational database; Python; Jupyter; Google Colab